Investigation of Turkish EFL Teachers' Views about Standard Languages, Dialects and Language Varieties through the lenses of English and Turkish - Ferhat Üresin; Ali Karakaş (Literacy Trek, 2019)
This study was set out to investigate a small number of Turkish EFL teachers' views about the concepts of a standard language, dialects, and other language varieties concerning their mother tongue (Turkish) and the language (English) they are tasked with teaching at schools. The respondents of this research were 12 Turkish EFL teachers working in a small province of Turkey. The data was collected through a questionnaire consisting of closed-ended and open-ended items about standard language, language varieties and dialects, taking Turkish and English as the focal reference points. The data was analysed through descriptive means and grouped under three main sections as, a) perceptions of a standard language, b) perceptions of dialects and other language varieties, and c) perceptions of Standard English and Standard Turkish. The findings indicated that there is some confusion among the EFL teachers as to making sense of the concept of standard language and the functions and the position of dialects and varieties in the society, particularly when it comes to instructional purposes. It was also found that most teachers acted under the influence of standard language ideology when conceptualising these concepts, with a strong attachment to the use of standard languages in formal settings. Overall, the findings imply that most teachers have a lack of awareness about the current sociolinguistic issues around English and Turkish, thereby not willing to give space to non-standard varieties and dialects in their teaching practices and real-life language use.